Cardiac safety of tiotropium in patients with cardiac events: a retrospective analysis of the UPLIFT® trial. Issue 1 (December 2015) - Tashkin, Donald; Leimer, Inge; Metzdorf, Norbert; Decramer, Marc
Abstract Background Tiotropium is an anticholinergic bronchodilator for symptom relief and reducing exacerbations with an established safety profile in patients with chronic obstructive pulmonary disease (COPD). Using data from the 4-year Understanding Potential Long-term Impacts on Function with Tiotropium (UPLIFT®) study, we re-evaluated the safety of tiotropium HandiHaler® in patients who experienced recent myocardial infarction (MI), heart failure or unstable rhythm disorder during the study. Methods Apost-hoc analysis of all-cause mortality and serious cardiac adverse events (cardiac SAEs), including cardiac deaths and death unknown, was conducted in patients who had experienced cardiac arrhythmia, MI or cardiac failure during UPLIFT® and who completed the study. Descriptive analyses were performed. Results Most patients experiencing cardiac events, for which they would have been excluded at baseline, remained in the trial. Kaplan-Meier analyses revealed a trend to later occurrence of cardiac SAEs with tiotropium HandiHaler® versus placebo. Patients who experienced a cardiac event and continued in UPLIFT® were not found to be at subsequently increased risk of all-cause mortality or cardiac SAEs with tiotropium treatment. Evaluation of deaths by major adverse cardiac events composite endpoints also showed that patients treated with tiotropium were not at increased risk of mortality or cardiac SAEs compared with placebo. Conclusions Risk of cardiac events, mortality or SAEs was not increased by tiotropium in patients experiencing cardiac events for which they would have been excluded at study baseline. The findings support the cardiac safety of tiotropium HandiHaler® in patients with COPD.